Back to Education: Psychopedagogical Strategies for Young Adults and Adults Returning to Secondary School through Distance Education (Revista Electrónica Calidad en la Educación Superior, 2025)
This article examines the need to implement psychopedagogical strategies for adults who return to secondary education through the National Distance Education School (CONED). According to the 2023 National Household Survey, 15.7% of Costa Ricans over the age of 24 have not completed secondary education, which limits their employment opportunities and perpetuates economic inequalities. The study, which is qualitative and descriptive in nature, reveals that the average age of these students is 35, and they have been out of the education system for 21 to 30 years before resuming their studies. These findings highlight the importance of adapting educational strategies to ensure their effective reintegration and academic success in distance education. The research focuses on the profile of CONED students, who face specific challenges due to the educational gap they have experienced.
Keywords: : distance education; secondary education; adult education; educational strategies; educational psychology